Sealant for display element, vertical conductive material, and display element

A sealant with specific surface energy and modulus properties, combined with curable resins, addresses air bubble intrusion in display elements, enhancing reliability in harsh environments.

JP7602437B2Active Publication Date: 2024-12-18SEKISUI CHEMICAL CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021112291
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-07-08
Filing Date
2021-07-06
Publication Date
2024-12-18
Estimated Expiration
2040-06-29

AI Technical Summary

Technical Problem

Display elements, such as liquid crystal and organic EL display elements, face reliability issues in high-temperature, high-humidity environments due to air bubble intrusion, which is not adequately addressed by existing sealants.

Method used

A sealant with a polar component term in the surface free energy equation of 6.0 or less and a storage modulus of 50 MPa or more at 121°C, containing specific curable resins and additives, is developed to prevent air bubble intrusion.

Benefits of technology

The sealant provides enhanced reliability in high-temperature, high-humidity conditions by suppressing air bubble intrusion and ensuring excellent moisture resistance and interfacial adhesion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602437000001
    Figure 0007602437000001
  • Figure 0007602437000002
    Figure 0007602437000002
Patent Text Reader

Abstract

To provide a sealant for display elements that gives a display element having excellent reliability under high-temperature and high-humidity environment, and also provide a vertical conductive material and a display element including the sealant for display elements.SOLUTION: A sealant for display elements contains a curable resin and a polymerization initiator and / or a thermosetting agent, where a polar component term of a cured product in the equation of surface free energy by the Owens-Wendt method is 6.0 or less, and a storage elastic modulus of the cured product at 121°C is 50 MPa or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sealant for display elements, which can provide a display element having excellent reliability even in a high-temperature and high-humidity environment, and also to a vertical conductive material and a display element using the sealant for display elements. [Background technology]

[0002] In recent years, liquid crystal display elements, organic EL display elements, and the like have been widely used as display elements having characteristics such as thinness, light weight, low power consumption, etc. In these display elements, the liquid crystal, light emitting layer, and the like are usually sealed with a sealant made of a curable resin composition. For example, as a liquid crystal display element, from the viewpoint of shortening the tact time and optimizing the amount of liquid crystal used, liquid crystal display elements using a light-heat curing type sealant as disclosed in Patent Documents 1 and 2 have been disclosed.

[0003] Display elements are also required to have high reliability when operated under high temperature and high humidity environments, and to perform in a pressure cooker test (PCT) under conditions of 121°C, 100% RH, and 2 atm. To obtain display elements with high reliability, it is necessary to use a sealant with excellent resistance to moisture and heat. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2001-133794 A [Patent Document 2] WO 02 / 092718 Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention aims to provide a sealant for a display element, which can provide a display element having excellent reliability even in a high-temperature and high-humidity environment, and to provide a vertical conductive material and a display element using the sealant for a display element. [Means for solving the problem]

[0006] The present invention provides a sealant for display elements which contains a curable resin and a polymerization initiator and / or a heat curing agent, and in which the polar component term in the surface free energy equation according to the Owens-Wendt method of the cured product is 6.0 or less, and the storage modulus of the cured product at 121°C is 50 MPa or more. The present invention will be described in detail below.

[0007] The present inventors confirmed that a display element that had a display defect when driven under a PCT (121°C, 100% RH, 2 atm) environment had had air bubbles infiltrate into the display element. The present inventors then investigated how to make the polar component term in the surface free energy equation according to the Owens-Wendt method of the cured product of the sealant for display elements be a specific value or less, and how to make the storage modulus of the cured product at 121°C be a specific value or more. As a result, they found that it is possible to obtain a sealant for display elements that can suppress the infiltration of air bubbles and provide a display element that is highly reliable in a high-temperature, high-humidity environment, and thus completed the present invention. The effect of the sealant for display elements of the present invention, that is, the ability to obtain a display element having excellent reliability even in a high-temperature and high-humidity environment, is particularly remarkable when the sealant for display elements of the present invention is used as a sealant for liquid crystal display elements.

[0008] The sealant for display elements of the present invention has a polar component term in the Owens-Wendt surface free energy equation of the cured product (hereinafter, simply referred to as "polar component term") of 6.0 or less. When the polar component term is 6.0 or less and the storage modulus of the cured product at 121°C is 50 MPa or more, the sealant for display elements of the present invention has an excellent effect of suppressing the intrusion of air bubbles in a high-temperature and high-humidity environment. The upper limit of the polar component term is preferably 5.7, and more preferably 5.3. Further, there is no particular preferred lower limit for the polar component term, but the substantial lower limit is 4.5. Specifically, the above polar component term can be calculated by measuring the contact angles of the cured product with water and methylene iodide (3 μL drop amount, 30 seconds after drop) using a contact angle meter at 25° C., and using the following formula. γs=γsd+γsp 72.8(1+cosθH)=2(21.8γsd) 1 / 2 +2(51.0γsp) 1 / 2 50.8(1+cosθI)=2(48.5γsd) 1 / 2 +2(2.3γsp) 1 / 2 γs: surface free energy γsd: Dispersion component of surface free energy γsp: Polar component of surface free energy θH: Contact angle with water θI: Contact angle with methylene iodide The following cured product is used for measuring the polar component term: A sealant is applied to one of two pieces of non-alkali glass, the other non-alkali glass is placed on top of the applied sealant, and a metal halide lamp is used to illuminate the cured product at 100 mW / cm2. 2 After irradiating the glass with ultraviolet light (wavelength 365 nm) for 30 seconds, one of the non-alkali glasses is peeled off and heated at 120°C for 1 hour to thermally cure the sealant. OA-10G (manufactured by Nippon Electric Glass Co., Ltd., thickness 0.7 mm, surface roughness 0.2 nmRa) is used as the non-alkali glass. Moreover, the contact angle meter may be, for example, a fully automatic contact angle meter DMo-701 (manufactured by Kyowa Interface Science Co., Ltd.).

[0009] The reason why the intrusion of air bubbles can be suppressed by using the sealant for display elements of the present invention is believed to be as follows. In other words, since the storage modulus of the cured product at 121°C, as described below, is 50 MPa or more, and the polar component term is 6.0 or less, the cured product itself not only has excellent moisture resistance, but also has high affinity with alignment films, etc., resulting in good interfacial adhesion, and it is presumed that as a result, the intrusion of moisture, which causes air bubbles, is suppressed.

[0010] The sealant for display elements of the present invention has a lower limit of storage modulus of 50 MPa at 121° C. of the cured product. Since the storage modulus of the cured product at 121° C. is 50 MPa or more and the polar component term is 6.0 or less, the sealant for display elements of the present invention has an excellent effect of suppressing the intrusion of air bubbles in a high-temperature and high-humidity environment. The lower limit of the storage modulus of the cured product at 121° C. is preferably 60 MPa, more preferably 80 MPa. The storage modulus of the cured product was measured using a sealant with a 100 mW / cm 2 The resin is exposed to ultraviolet light for 30 seconds, then heated at 120°C for 1 hour to harden it. The storage modulus can be measured using a dynamic viscoelasticity measuring device under the conditions of a test piece width of 5 mm, a thickness of 0.35 mm, a grip width of 25 mm, a heating rate of 10° C. / min, and a frequency of 5 Hz. The dynamic viscoelasticity measuring device may be, for example, DVA-200 (manufactured by IT Measurement & Control Co., Ltd.).

[0011] In the sealant for display elements of the present invention, a method for adjusting the polar component term and the storage modulus at 121°C of the cured product to the above-mentioned ranges is preferably a method for adjusting the type and content ratio of each of the constituent components contained in the sealant for display elements.

[0012] The sealant for a display element of the present invention contains a curable resin. The curable resin preferably contains a compound having an epoxy group. By including the compound having an epoxy group, the resulting sealant for display elements has an excellent effect of suppressing the intrusion of air bubbles under a high-temperature and high-humidity environment.

[0013] Examples of the compound having an epoxy group include bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, bisphenol S type epoxy compounds, 2,2'-diallyl bisphenol A type epoxy compounds, hydrogenated bisphenol type epoxy compounds, propylene oxide-added bisphenol A type epoxy compounds, resorcinol type epoxy compounds, biphenyl type epoxy compounds, sulfide type epoxy compounds, diphenyl ether type epoxy compounds, dicyclopentadiene type epoxy compounds, naphthalene type epoxy compounds, phenol novolac type epoxy compounds, ortho-cresol novolac type epoxy compounds, dicyclopentadiene novolac type epoxy compounds, biphenyl novolac type epoxy compounds, naphthalene phenol novolac type epoxy compounds, glycidyl amine type epoxy compounds, alkyl polyol type epoxy compounds, rubber-modified type epoxy compounds, and glycidyl ester compounds.

[0014] Among the above bisphenol A type epoxy compounds, commercially available ones include, for example, jER828EL, jER1004 (both manufactured by Mitsubishi Chemical Corporation), EPICLON EXA-850CRP (manufactured by DIC Corporation), and the like. Among the above bisphenol F type epoxy compounds, commercially available ones include, for example, jER806, jER4004 (both manufactured by Mitsubishi Chemical Corporation), EPICLON EXA-830CRP (manufactured by DIC Corporation), and the like. Among the above bisphenol S type epoxy compounds, commercially available ones include, for example, EPICLON EXA1514 (manufactured by DIC Corporation). Among the above 2,2'-diallylbisphenol A type epoxy compounds, a commercially available example is RE-810NM (manufactured by Nippon Kayaku Co., Ltd.). Among the above hydrogenated bisphenol type epoxy compounds, commercially available ones include, for example, EPICLON EXA7015 (manufactured by DIC Corporation). Among the above propylene oxide-added bisphenol A type epoxy compounds, commercially available ones include, for example, EP-4000S (manufactured by ADEKA Corporation). Among the above resorcinol type epoxy compounds, a commercially available example is EX-201 (manufactured by Nagase ChemteX Corporation). Among the biphenyl type epoxy compounds, examples of commercially available compounds include jER YX-4000H (manufactured by Mitsubishi Chemical Corporation). Among the above sulfide type epoxy compounds, a commercially available example is YSLV-50TE (manufactured by Nippon Steel Chemical & Material Co., Ltd.). Among the diphenyl ether type epoxy compounds, a commercially available example is YSLV-80DE (manufactured by Nippon Steel Chemical & Material Co., Ltd.). Among the above dicyclopentadiene type epoxy compounds, commercially available ones include, for example, EP-4088S (manufactured by ADEKA Corporation). Among the above naphthalene type epoxy compounds, commercially available ones include, for example, EPICLON HP4032, EPICLON EXA-4700 (both manufactured by DIC Corporation), and the like. Among the above phenol novolac type epoxy compounds, a commercially available example is EPICLON N-770 (manufactured by DIC Corporation). Among the above ortho-cresol novolac type epoxy compounds, a commercially available example is EPICLON N-670-EXP-S (manufactured by DIC Corporation). Among the above dicyclopentadiene novolac type epoxy compounds, a commercially available example is EPICLON HP7200 (manufactured by DIC Corporation). Among the biphenyl novolac type epoxy compounds, a commercially available example is NC-3000P (manufactured by Nippon Kayaku Co., Ltd.). Among the above naphthalenephenol novolac type epoxy compounds, a commercially available example is ESN-165S (manufactured by Nippon Steel Chemical & Material Co., Ltd.). Among the above glycidylamine type epoxy compounds, commercially available ones include, for example, jER630 (manufactured by Mitsubishi Chemical Corporation), EPICLON 430 (manufactured by DIC Corporation), TETRAD-X (manufactured by Mitsubishi Gas Chemical Company, Inc.), and the like. Commercially available examples of the alkyl polyol type epoxy compounds include ZX-1542 (manufactured by Nippon Steel Chemical & Materials Co., Ltd.), EPICLON 726 (manufactured by DIC Corporation), Epolite 80MFA (manufactured by Kyoeisha Chemical Co., Ltd.), and Denacol EX-611 (manufactured by Nagase ChemteX Corporation). Among the above rubber-modified epoxy compounds, commercially available ones include, for example, YR-450, YR-207 (both manufactured by Nippon Steel Chemical & Material Co., Ltd.), Epolead PB (manufactured by Daicel Corporation), and the like. Among the above glycidyl ester compounds, commercially available ones include, for example, Denacol EX-147 (manufactured by Nagase Chemtex Corporation). Other commercially available compounds having an epoxy group include, for example, YDC-1312, YSLV-80XY, YSLV-90CR (all manufactured by Nippon Steel Chemical & Material Co., Ltd.), XAC4151 (manufactured by Asahi Kasei Corporation), jER1031, jER1032 (all manufactured by Mitsubishi Chemical Corporation), EXA-7120 (manufactured by DIC Corporation), and TEPIC (manufactured by Nissan Chemical Industries, Ltd.).

[0015] As the compound having an epoxy group, a partially (meth)acrylic modified epoxy compound is also suitably used. In this specification, the partially (meth)acrylic modified epoxy compound means a compound having one or more epoxy groups and one or more (meth)acryloyl groups in one molecule, which can be obtained by reacting a portion of the epoxy groups of a compound having two or more epoxy groups with (meth)acrylic acid. In this specification, the above "(meth)acryloyl" means acryloyl or methacryloyl.

[0016] Among the partially (meth)acrylic modified epoxy compounds, commercially available ones include, for example, UVACURE1561, KRM8287 (both manufactured by Daicel-Allnex Corporation), MEM-5000H (manufactured by Neo Chemical Corporation), and the like.

[0017] The preferred lower limit of the content of the compound having an epoxy group in 100 parts by weight of the curable resin is 10 parts by weight, and the preferred upper limit is 60 parts by weight. When the content of the compound having an epoxy group is 10 parts by weight or more, the resulting sealant for display elements has a better effect of suppressing the intrusion of air bubbles in a high-temperature and high-humidity environment. When the content of the compound having an epoxy group is 60 parts by weight or less, the resulting sealant for display elements has a better low liquid crystal contamination property when used as a sealant for liquid crystal display elements. The more preferred lower limit of the content of the compound having an epoxy group is 20 parts by weight, and the more preferred upper limit is 40 parts by weight.

[0018] The curable resin preferably contains a (meth)acrylic compound. Examples of the (meth)acrylic compound include (meth)acrylic acid ester compounds, epoxy (meth)acrylates, and urethane (meth)acrylates. Among these, epoxy (meth)acrylates are preferred. In addition, the (meth)acrylic compound is preferably one having two or more (meth)acryloyl groups in one molecule from the viewpoint of reactivity. In this specification, the term "(meth)acrylic" refers to acrylic or methacrylic, and the term "(meth)acrylic compound" refers to a compound having a (meth)acryloyl group. The term "(meth)acrylate" refers to acrylate or methacrylate, and the term "epoxy (meth)acrylate" refers to a compound in which all epoxy groups in an epoxy compound are reacted with (meth)acrylic acid.

[0019] The curable resin preferably contains a compound having a methacryloyl group as the (meth)acrylic compound, since this makes it easier to set the glass transition temperature of the cured product of the resulting sealant for display elements in the range described below. When the curable resin contains the compound having the methacryloyl group, the methacryl ratio represented by the following formula (I) is preferably 0.3 or more. By having the methacryl ratio of 0.3 or more, it becomes easier to set the glass transition temperature of the cured product of the obtained sealant for display elements to the range described below. The methacryl ratio is more preferably 0.5 or more, and even more preferably 0.6 or more. Methacrylic ratio = (W M / E M ) / (W A / E A +W M / E M ) (I) In formula (I), E A is the acryloyl group equivalent (g / mol) of a compound having an acryloyl group, and E M is the methacryloyl group equivalent (g / mol) of a compound having a methacryloyl group, and W A is the content (parts by weight) of the compound having an acryloyl group, and W M is the content (parts by weight) of the compound having a methacryloyl group. The "acryloyl group equivalent" is a value obtained by dividing the weight (g) of a compound having an acryloyl group by the number of moles (mol) of acryloyl groups contained in the compound having an acryloyl group. When the curable resin contains a plurality of compounds (A1, A2, ...) having an acryloyl group, "W A / E A " is the sum of the values ​​obtained by dividing the content of each compound having an acryloyl group by the acryloyl group equivalent (W A1 / E A1 +W A2 / E A2 In the case where the curable resin does not contain the compound having an acryloyl group, "W A / E A " is set to 0. The "methacryloyl group equivalent" is a value obtained by dividing the weight (g) of a compound having a methacryloyl group by the number of moles (mol) of the methacryloyl group contained in the compound having a methacryloyl group. When the curable resin contains a plurality of compounds having a methacryloyl group (M1, M2, ...), the "W M / E M " is the sum of the values ​​obtained by dividing the content of each compound having a methacryloyl group by the methacryloyl group equivalent (W M1 / E M1 +W M2 / E M2 +···).

[0020] Examples of the monofunctional (meth)acrylic acid ester compounds include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, and isoctyl (meth)acrylate. Somyristyl (meth)acrylate, stearyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, bicyclopentenyl (meth)acrylate, benzyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2 -Butoxyethyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, methoxyethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, ethyl carbitol (meth)acrylate, 2,2,2-trifluoroethyl (meth)acrylate, 2,2,3,3-tetrafluoropropionate Examples of the acrylates include 2-(meth)acryloyloxyethyl 2-hydroxypropyl phthalate, 2-(meth)acryloyloxyethyl 2-hydroxypropyl phthalate, 2-(meth)acryloyloxyethyl phosphate, and glycidyl (meth)acrylate.

[0021] Examples of the bifunctional (meth)acrylic acid ester compounds include 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, 2-n-butyl-2-ethyl-1,3-propanediol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, and the like. Examples of the di(meth)acrylate include butyl di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethylene oxide-added bisphenol A di(meth)acrylate, propylene oxide-added bisphenol A di(meth)acrylate, ethylene oxide-added bisphenol F di(meth)acrylate, dimethylol dicyclopentadienyl di(meth)acrylate, ethylene oxide-modified isocyanuric acid di(meth)acrylate, 2-hydroxy-3-(meth)acryloyloxypropyl (meth)acrylate, carbonate diol di(meth)acrylate, polyether diol di(meth)acrylate, polyester diol di(meth)acrylate, polycaprolactone diol di(meth)acrylate, and polybutadiene diol di(meth)acrylate.

[0022] In addition, examples of the (meth)acrylic acid ester compounds having three or more functional groups include trimethylolpropane tri(meth)acrylate, ethylene oxide-added trimethylolpropane tri(meth)acrylate, propylene oxide-added trimethylolpropane tri(meth)acrylate, caprolactone-modified trimethylolpropane tri(meth)acrylate, ethylene oxide-added isocyanuric acid tri(meth)acrylate, glycerin tri(meth)acrylate, propylene oxide-added glycerin tri(meth)acrylate, pentaerythritol tri(meth)acrylate, tris(meth)acryloyloxyethyl phosphate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate.

[0023] The epoxy (meth)acrylate may, for example, be one obtained by reacting an epoxy compound with (meth)acrylic acid in the presence of a basic catalyst according to a conventional method.

[0024] Examples of epoxy compounds that serve as raw materials for synthesizing the above-mentioned epoxy (meth)acrylates include bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, bisphenol S type epoxy compounds, 2,2'-diallyl bisphenol A type epoxy compounds, hydrogenated bisphenol type epoxy compounds, propylene oxide-added bisphenol A type epoxy compounds, resorcinol type epoxy compounds, biphenyl type epoxy compounds, sulfide type epoxy compounds, diphenyl ether type epoxy compounds, dicyclopentadiene type epoxy compounds, naphthalene type epoxy compounds, phenol novolac type epoxy compounds, ortho-cresol novolac type epoxy compounds, dicyclopentadiene novolac type epoxy compounds, biphenyl novolac type epoxy compounds, naphthalene phenol novolac type epoxy compounds, glycidyl amine type epoxy compounds, alkyl polyol type epoxy compounds, rubber-modified type epoxy compounds, and glycidyl ester compounds.

[0025] Among the above epoxy (meth)acrylates, commercially available ones include, for example, epoxy (meth)acrylate manufactured by Daicel-Allnex Corporation, epoxy (meth)acrylate manufactured by Shin-Nakamura Chemical Co., Ltd., epoxy (meth)acrylate manufactured by Kyoeisha Chemical Co., Ltd., epoxy (meth)acrylate manufactured by Nagase ChemteX Corporation, and epoxy (meth)acrylate manufactured by KSM Corporation. Examples of the epoxy (meth)acrylates manufactured by Daicel-Allnex include EBECRYL860, EBECRYL3200, EBECRYL3201, EBECRYL3412, EBECRYL3600, EBECRYL3700, EBECRYL3701, EBECRYL3702, EBECRYL3703, EBECRYL3708, EBECRYL3800, EBECRYL6040, and EBECRYL RDX63182. Examples of the epoxy (meth)acrylates manufactured by Shin-Nakamura Chemical Co., Ltd. include EA-1010, EA-1020, EA-5323, EA-5520, EA-CHD, and EMA-1020. Examples of the epoxy (meth)acrylates manufactured by Kyoeisha Chemical Co., Ltd. include Epoxy Ester M-600A, Epoxy Ester 40EM, Epoxy Ester 70PA, Epoxy Ester 200PA, Epoxy Ester 80MFA, Epoxy Ester 3002M, Epoxy Ester 3002A, Epoxy Ester 1600A, Epoxy Ester 3000M, Epoxy Ester 3000A, Epoxy Ester 200EA, and Epoxy Ester 400EA. Examples of the epoxy (meth)acrylates manufactured by Nagase ChemteX Corporation include Denacol Acrylate DA-141, Denacol Acrylate DA-314, and Denacol Acrylate DA-911. An example of the epoxy (meth)acrylate manufactured by KSM Co., Ltd. is BAEM-100.

[0026] The urethane (meth)acrylate can be obtained, for example, by reacting a polyfunctional isocyanate compound with a (meth)acrylic acid derivative having a hydroxyl group in the presence of a catalytic amount of a tin compound.

[0027] Examples of the polyfunctional isocyanate compound include isophorone diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, diphenylmethane-4,4'-diisocyanate (MDI), hydrogenated MDI, polymeric MDI, 1,5-naphthalene diisocyanate, norbornane diisocyanate, tolidine diisocyanate, xylylene diisocyanate (XDI), hydrogenated XDI, lysine diisocyanate, triphenylmethane triisocyanate, tris(isocyanatephenyl)thiophosphate, tetramethylxylylene diisocyanate, and 1,6,11-undecane triisocyanate.

[0028] As the polyfunctional isocyanate compound, a chain-extended polyfunctional isocyanate compound obtained by reacting a polyol with an excess of the polyfunctional isocyanate compound can also be used. Examples of the polyol include ethylene glycol, propylene glycol, glycerin, sorbitol, trimethylolpropane, carbonate diol, polyether diol, polyester diol, and polycaprolactone diol.

[0029] Examples of the (meth)acrylic acid derivative having a hydroxyl group include hydroxyalkyl mono(meth)acrylates, mono(meth)acrylates of dihydric alcohols, mono(meth)acrylates or di(meth)acrylates of trihydric alcohols, and epoxy (meth)acrylates. Examples of the hydroxyalkyl mono(meth)acrylate include 2-hydroxyethyl(meth)acrylate, 2-hydroxypropyl(meth)acrylate, 2-hydroxybutyl(meth)acrylate, and 4-hydroxybutyl(meth)acrylate. Examples of the dihydric alcohol include ethylene glycol, propylene glycol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, and polyethylene glycol. Examples of the trihydric alcohol include trimethylolethane, trimethylolpropane, and glycerin. The epoxy (meth)acrylate may, for example, be bisphenol A type epoxy acrylate.

[0030] Among the above urethane (meth)acrylates, commercially available ones include, for example, urethane (meth)acrylate manufactured by Toagosei Co., Ltd., urethane (meth)acrylate manufactured by Daicel-Allnex Corporation, urethane (meth)acrylate manufactured by Negami Chemical Industries Co., Ltd., urethane (meth)acrylate manufactured by Shin-Nakamura Chemical Co., Ltd., and urethane (meth)acrylate manufactured by Kyoeisha Chemical Co., Ltd. Examples of the urethane (meth)acrylates manufactured by Toagosei Co., Ltd. include M-1100, M-1200, M-1210, and M-1600. Examples of the urethane (meth)acrylates manufactured by Daicel-Allnex include EBECRYL210, EBECRYL220, EBECRYL230, EBECRYL270, EBECRYL1290, EBECRYL2220, EBECRYL4827, EBECRYL4842, EBECRYL4858, EBECRYL5129, EBECRYL6700, EBECRYL8402, EBECRYL8803, EBECRYL8804, EBECRYL8807, EBECRYL9260, and the like. Examples of the urethane (meth)acrylates manufactured by Negami Chemical Industrial Co., Ltd. include Art Resin UN-330, Art Resin SH-500B, Art Resin UN-1200TPK, Art Resin UN-1255, Art Resin UN-3320HB, Art Resin UN-7100, Art Resin UN-9000A, Art Resin UN-9000H, etc. Examples of the urethane (meth)acrylates manufactured by Shin-Nakamura Chemical Co., Ltd. include U-2HA, U-2PHA, U-3HA, U-4HA, U-6H, U-6HA, U-6LPA, U-10H, U-15HA, U-108, U-108A, U-122A, U-122P, U-324A, U-340A, U-340P, U-1084A, U-2061BA, UA-340P, UA-4000, UA-4100, UA-4200, UA-4400, UA-5201P, UA-7100, UA-7200, and UA-W2A. Examples of the urethane (meth)acrylates manufactured by Kyoeisha Chemical Co., Ltd. include AH-600, AI-600, AT-600, UA-101I, UA-101T, UA-306H, UA-306I, and UA-306T.

[0031] The curable resin preferably contains a compound having a flexible skeleton, more preferably an epoxy compound having a flexible skeleton and / or a (meth)acrylic compound having a flexible skeleton. By using such a compound having a flexible skeleton, it becomes easier to set the storage modulus at 121°C of the cured product to the above-mentioned range.

[0032] The flexible skeleton is preferably at least one selected from the group consisting of an open-ring lactone structure, an alkylene oxide structure, and a rubber structure, and more preferably a open-ring lactone structure. In this specification, the "rubber structure" refers to a structure that exhibits rubber elasticity, such as a vulcanized rubber structure formed by adding sulfur to raw rubber, a synthetic rubber structure with double bonds formed in the molecular main chain by addition polymerization, or a silicone rubber structure formed by crosslinking polymethylsiloxane using a peroxide.

[0033] Examples of the lactone include γ-undecalactone, ε-caprolactone, γ-decalactone, σ-dodecalactone, γ-nonalactone, γ-nonanolactone, γ-valerolactone, σ-valerolactone, β-butyrolactone, γ-butyrolactone, β-propiolactone, σ-hexanolactone, 7-butyl-2-oxepanone, etc. Among these, those having a linear portion of the main skeleton with 5 to 7 carbon atoms when ring-opened are preferred.

[0034] Examples of the alkylene oxide structure include an ethylene oxide structure, a propylene oxide structure, and a butylene oxide structure.

[0035] The rubber structure is preferably a structure having an unsaturated bond in the main chain, or a structure having a polysiloxane skeleton in the main chain. The structure having an unsaturated bond in the main chain includes, for example, a structure having a skeleton formed by polymerization of a conjugated diene in the main chain. Examples of the skeleton formed by polymerization of the conjugated diene include an acrylonitrile-butadiene skeleton, a polybutadiene skeleton, a polyisoprene skeleton, a styrene-butadiene skeleton, a polyisobutylene skeleton, and a polychloroprene skeleton.

[0036] The preferred lower limit of the content of the compound having a flexible skeleton in 100 parts by weight of the curable resin is 5 parts by weight, and the preferred upper limit is 30 parts by weight. By setting the content of the compound having a flexible skeleton within this range, it becomes easier to set the storage modulus at 121°C of the cured product of the sealant for display elements to the above-mentioned range. The more preferred lower limit of the content of the compound having a flexible skeleton is 10 parts by weight, and the more preferred upper limit is 20 parts by weight.

[0037] The sealant for a display element of the present invention contains a polymerization initiator and / or a heat curing agent. Examples of the polymerization initiator include a radical polymerization initiator and a cationic polymerization initiator.

[0038] Examples of the radical polymerization initiator include a photoradical polymerization initiator which generates radicals upon irradiation with light, and a thermal radical polymerization initiator which generates radicals upon heating.

[0039] Examples of the photoradical polymerization initiator include benzophenone-based compounds, acetophenone-based compounds, acylphosphine oxide-based compounds, titanocene-based compounds, oxime ester-based compounds, benzoin ether-based compounds, and thioxanthone-based compounds. Specific examples of the photoradical polymerization initiator include 1-hydroxycyclohexyl phenyl ketone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone, 2-(dimethylamino)-2-((4-methylphenyl)methyl)-1-(4-(4-morpholinyl)phenyl)-1-butanone, 2,2-dimethoxy-1,2-diphenylethan-1-one, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2-methyl-1,2-diphenylethan-1-one ... ethyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, 1-(4-(2-hydroxyethoxy)-phenyl)-2-hydroxy-2-methyl-1-propan-1-one, 1-(4-(phenylthio)phenyl)-1,2-octanedione 2-(O-benzoyloxime), 2,4,6-trimethylbenzoyldiphenylphosphine oxide, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and the like.

[0040] Examples of the thermal radical polymerization initiator include those composed of an azo compound, an organic peroxide, etc. Among them, a polymeric azo initiator composed of a polymeric azo compound is preferred. In this specification, the polymeric azo compound refers to a compound that has an azo group, generates radicals capable of curing a (meth)acryloyloxy group by heat, and has a number average molecular weight of 300 or more.

[0041] The number average molecular weight of the polymer azo compound is preferably 1000 at the lower limit and 300,000 at the upper limit. The number average molecular weight of the polymer azo compound is within this range, so that the polymer azo compound can be easily mixed into a curable resin, and when the resulting sealant for display elements is used in a liquid crystal display element, adverse effects on the liquid crystal can be prevented. The number average molecular weight of the polymer azo compound is more preferably 5000 at the lower limit and 100,000 at the upper limit, and even more preferably 10,000 at the lower limit and 90,000 at the upper limit. In this specification, the number average molecular weight is a value obtained by measuring using tetrahydrofuran as a solvent by gel permeation chromatography (GPC) and converting the molecular weight into polystyrene equivalent. Examples of columns used for measuring the number average molecular weight converted into polystyrene equivalent by GPC include Shodex LF-804 (manufactured by Showa Denko KK).

[0042] Examples of the polymeric azo compound include those having a structure in which a plurality of units such as polyalkylene oxide and polydimethylsiloxane are bonded via azo groups. As the polymeric azo compound having a structure in which a plurality of units such as polyalkylene oxide are bonded via the azo group, those having a polyethylene oxide structure are preferred. Specific examples of the polymeric azo compound include a polycondensate of 4,4'-azobis(4-cyanopentanoic acid) and polyalkylene glycol, and a polycondensate of 4,4'-azobis(4-cyanopentanoic acid) and polydimethylsiloxane having a terminal amino group. Among the above polymeric azo compounds, commercially available ones include, for example, VPE-0201, VPE-0401, VPE-0601, VPS-0501, and VPS-1001 (all manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.). In addition, examples of commercially available non-polymeric azo compounds include V-65 and V-501 (both manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.).

[0043] Examples of the organic peroxide include ketone peroxides, peroxyketals, hydroperoxides, dialkyl peroxides, peroxy esters, diacyl peroxides, and peroxydicarbonates.

[0044] As the cationic polymerization initiator, a photocationic polymerization initiator can be suitably used. The photocationic polymerization initiator is not particularly limited as long as it generates a protonic acid or a Lewis acid upon irradiation with light, and may be an ionic photoacid generating type or a nonionic photoacid generating type. Examples of the photocationic polymerization initiator include onium salts such as aromatic diazonium salts, aromatic halonium salts, and aromatic sulfonium salts; and organometallic complexes such as iron-allene complexes, titanocene complexes, and arylsilanol-aluminum complexes.

[0045] Among the above-mentioned photocationic polymerization initiators, examples of commercially available ones include ADEKA OPTOMER SP-150 and ADEKA OPTOMER SP-170 (both manufactured by ADEKA Corporation).

[0046] The polymerization initiators may be used alone or in combination of two or more kinds.

[0047] The content of the polymerization initiator is preferably 0.1 parts by weight at the lower limit and 30 parts by weight at the upper limit with respect to 100 parts by weight of the curable resin. When the content of the polymerization initiator is 0.1 parts by weight or more, the obtained sealant for display elements has better curability. When the content of the polymerization initiator is 30 parts by weight or less, the obtained sealant for display elements has better storage stability. The more preferred lower limit of the content of the polymerization initiator is 1 part by weight, the more preferred upper limit is 10 parts by weight, and the even more preferred upper limit is 5 parts by weight.

[0048] Examples of the heat curing agent include organic acid hydrazides, imidazole derivatives, amine compounds, polyhydric phenol compounds, acid anhydrides, etc. Among these, solid organic acid hydrazides are preferably used. The above heat curing agents may be used alone or in combination of two or more kinds.

[0049] Examples of the solid organic acid hydrazide include 1,3-bis(hydrazinocarboethyl)-5-isopropylhydantoin, sebacic acid dihydrazide, isophthalic acid dihydrazide, adipic acid dihydrazide, and malonic acid dihydrazide. Among the above organic acid hydrazides, examples of commercially available ones include organic acid hydrazides manufactured by Otsuka Chemical Co., Ltd., organic acid hydrazides manufactured by Japan FineChem Co., Ltd., and organic acid hydrazides manufactured by Ajinomoto Fine-Techno Co., Ltd. Examples of the organic acid hydrazides available from Otsuka Chemical Co., Ltd. include SDH and ADH. The organic acid hydrazide manufactured by Japan Finechem Co., Ltd. is, for example, MDH. Examples of the organic acid hydrazides manufactured by Ajinomoto Fine-Techno Co., Inc. include Amicure VDH, Amicure VDH-J, and Amicure UDH.

[0050] The content of the heat curing agent is preferably 1 part by weight at the lower limit and 50 parts by weight at the upper limit relative to 100 parts by weight of the curable resin. When the content of the heat curing agent is 1 part by weight or more, the obtained sealant for display elements has better heat curing properties. When the content of the heat curing agent is 50 parts by weight or less, the obtained sealant for display elements has better coatability and storage stability. The more preferred upper limit of the content of the heat curing agent is 30 parts by weight.

[0051] The sealant for display elements of the present invention preferably contains a filler for the purposes of adjusting viscosity, improving adhesion by a stress dispersion effect, improving the linear expansion coefficient, and improving the moisture resistance of the cured product.

[0052] As the filler, an inorganic filler or an organic filler can be used. Examples of the inorganic filler include silica, talc, glass beads, asbestos, gypsum, diatomaceous earth, smectite, bentonite, montmorillonite, sericite, activated clay, alumina, zinc oxide, iron oxide, magnesium oxide, tin oxide, titanium oxide, calcium carbonate, magnesium carbonate, magnesium hydroxide, aluminum hydroxide, aluminum nitride, silicon nitride, barium sulfate, and calcium silicate. Examples of the organic filler include polyester fine particles, polyurethane fine particles, vinyl polymer fine particles, and acrylic polymer fine particles.

[0053] The preferred lower limit of the content of the filler in 100 parts by weight of the sealant for display elements of the present invention is 10 parts by weight, and the preferred upper limit is 70 parts by weight. By having the content of the filler in this range, it is possible to suppress deterioration of the coating property, etc., while more effectively improving the adhesiveness, etc. The more preferred lower limit of the content of the filler is 20 parts by weight, and the more preferred upper limit is 60 parts by weight.

[0054] The sealant for display elements of the present invention preferably contains a silane coupling agent. The silane coupling agent mainly serves as an adhesion aid for providing good adhesion between the sealant and a substrate or the like.

[0055] Suitable examples of the silane coupling agent include 3-mercaptopropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-isocyanatopropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, etc. These silane coupling agents are excellent in improving adhesion to a substrate, etc., and when the resulting sealant for display elements is used in a liquid crystal display element, it is possible to suppress outflow of the curable resin into the liquid crystal. The above silane coupling agents may be used alone or in combination of two or more kinds.

[0056] The content of the silane coupling agent in 100 parts by weight of the sealant for display elements of the present invention is preferably 0.1 parts by weight at the lower limit and 10 parts by weight at the upper limit. By the content of the silane coupling agent being within this range, the resulting sealant for display elements has better adhesion, and when the resulting sealant for display elements is used for a liquid crystal display element, the occurrence of liquid crystal contamination can be suppressed. The content of the silane coupling agent is more preferably 0.3 parts by weight at the lower limit and 5 parts by weight at the upper limit.

[0057] The sealant for a display element of the present invention may contain the above-mentioned light-shielding agent. By containing the above-mentioned light-shielding agent, the sealant for a display element of the present invention can be suitably used as a light-shielding sealant.

[0058] Examples of the light-shielding agent include iron oxide, titanium black, aniline black, cyanine black, fullerene, carbon black, resin-coated carbon black, etc. Among these, titanium black is preferable. The above light-shielding agents may be used alone or in combination of two or more kinds.

[0059] The titanium black is a substance that has a higher transmittance for light near the ultraviolet region, particularly light with a wavelength of 370 nm or more and 450 nm or less, compared to the average transmittance for light with a wavelength of 300 nm or more and 800 nm or less. That is, the titanium black is a light-shielding agent that imparts light-shielding properties to the sealant for display elements of the present invention by sufficiently blocking light with wavelengths in the visible light region, while allowing light with wavelengths near the ultraviolet region to pass through. As the light-shielding agent contained in the sealant for display elements of the present invention, a substance with high insulating properties is preferred, and titanium black is also suitable as a light-shielding agent with high insulating properties.

[0060] Although the titanium black exhibits sufficient effects even when not surface-treated, it is also possible to use titanium black whose surface has been treated with an organic component such as a coupling agent, or titanium black whose surface has been coated with an inorganic component such as silicon oxide, titanium oxide, germanium oxide, aluminum oxide, zirconium oxide, magnesium oxide, etc. Among these, titanium black treated with an organic component is preferred in that it can further improve insulation properties. Furthermore, a display element manufactured using the sealing agent for display elements of the present invention, which contains the above-mentioned titanium black as a light-blocking agent, has sufficient light-blocking properties, and therefore can realize a display element with no light leakage, high contrast, and excellent image display quality.

[0061] Among the titanium blacks mentioned above, commercially available titanium blacks include, for example, titanium black manufactured by Mitsubishi Materials Corporation and titanium black manufactured by Ako Kasei Co., Ltd. Examples of the titanium black manufactured by Mitsubishi Materials Corporation include 12S, 13M, 13M-C, 13R-N, and 14M-C. An example of the titanium black manufactured by Ako Kasei Co., Ltd. is Tilac D.

[0062] The preferred lower limit of the specific surface area of ​​the titanium black is 13 m 2 / g, with a preferred upper limit of 30m 2 / g, and a more preferable lower limit is 15m 2 / g, with a more preferable upper limit of 25m 2 / g. The volume resistivity of the titanium black preferably has a lower limit of 0.5 Ω·cm and a higher limit of 3 Ω·cm, more preferably a lower limit of 1 Ω·cm and a more preferably upper limit of 2.5 Ω·cm.

[0063] The primary particle diameter of the light-shielding agent is not particularly limited as long as it is equal to or smaller than the distance between the substrates of the display element, but the preferred lower limit is 1 nm, and the preferred upper limit is 5000 nm. By setting the primary particle diameter of the light-shielding agent within this range, the obtained sealant for display elements can have excellent light-shielding properties without deteriorating the drawing properties, etc. The more preferred lower limit of the primary particle diameter of the light-shielding agent is 5 nm, the more preferred upper limit is 200 nm, the even more preferred lower limit is 10 nm, and the even more preferred upper limit is 100 nm. The primary particle size of the light-shielding agent can be measured by dispersing the light-shielding agent in a solvent (water, organic solvent, etc.) using NICOMP 380ZLS (manufactured by PARTICLE SIZING SYSTEMS).

[0064] The preferred lower limit of the content of the light-shielding agent in 100 parts by weight of the sealant for display elements of the present invention is 5 parts by weight, and the preferred upper limit is 80 parts by weight. By having the content of the light-shielding agent in this range, the adhesiveness, strength after curing, and drawing property of the resulting sealant for display elements are suppressed from deteriorating, and the effect of improving the light-shielding property is more excellent. The more preferred lower limit of the content of the light-shielding agent is 10 parts by weight, and the more preferred upper limit is 70 parts by weight, and the even more preferred lower limit is 30 parts by weight, and the even more preferred upper limit is 60 parts by weight.

[0065] The sealant for display elements of the present invention may further contain additives such as a reactive diluent, a spacer, a curing accelerator, a defoamer, a leveling agent, a polymerization inhibitor, and other coupling agents, if necessary.

[0066] An example of a method for producing the sealant for display elements of the present invention is a method in which a curable resin, a polymerization initiator and / or a heat curing agent, and a silane coupling agent, which is added as necessary, are mixed using a mixer. Examples of the mixer include a homodisper, a homomixer, a universal mixer, a planetary mixer, a kneader, and a three-roll mixer.

[0067] The display element sealant of the present invention has a preferred lower limit of the glass transition temperature of the cured product of 125° C. When the glass transition temperature of the cured product is 125° C. or higher, the resulting display element sealant has a superior effect of suppressing the intrusion of air bubbles in a high-temperature and high-humidity environment. The more preferred lower limit of the glass transition temperature of the cured product is 130° C. From the viewpoint of adhesion, the upper limit of the glass transition temperature of the cured product is preferably 170°C. In this specification, the "glass transition temperature" refers to the temperature at which the maximum due to micro-Brownian motion appears among the maximum loss tangents (tan δ) obtained by dynamic viscoelasticity measurement. The glass transition temperature can be measured by a conventional method using a dynamic viscoelasticity measuring device or the like. The cured product for measuring the glass transition temperature was a sealant with a 100 mW / cm 2 The resin is exposed to ultraviolet light for 30 seconds, then heated at 120°C for 1 hour to harden it.

[0068] The sealant for display elements of the present invention preferably has a water absorption rate of 4.0% by weight or less after a high-temperature, high-humidity test in which the cured product is exposed to an environment of 121°C, 100% RH, and 2 atm for 24 hours. When the water absorption rate is 4.0% by weight or less, the sealant for display elements of the present invention has a superior effect of suppressing the intrusion of air bubbles in a high-temperature, high-humidity environment. The upper limit of the water absorption rate is more preferably 3.0% by weight, and even more preferably 2.5% by weight. Although there is no particular preferred lower limit for the water absorption rate, the substantial lower limit is 1.0% by weight. The above "water absorption rate" is the weight before the high temperature and high humidity test. 1 , the weight after high temperature and high humidity test is W 2 In this case, it is calculated using the following formula. Water absorption rate (weight %) = ((W 2 -W 1 ) / W 1 ) x 100 The cured product for measuring the water absorption rate was a sealant with a 100 mW / cm 2The resin is exposed to ultraviolet light for 30 seconds, then heated at 120°C for 1 hour to harden it.

[0069] A vertical conductive material can be produced by blending conductive fine particles with the sealant for display elements of the present invention. Such a vertical conductive material containing the sealant for display elements of the present invention and conductive fine particles also constitutes the present invention.

[0070] The conductive fine particles are not particularly limited, and may be metal balls, fine resin particles having a conductive metal layer formed on the surface thereof, etc. Among them, fine resin particles having a conductive metal layer formed on the surface thereof are preferred because they have excellent elasticity and can provide conductive connection without damaging a transparent substrate, etc.

[0071] The present invention also includes a display element having a cured product of the sealant for display elements of the present invention or a cured product of the vertical conductive material of the present invention.The display element of the present invention is preferably a liquid crystal display element. As a method for producing a liquid crystal display element using the sealant for a display element of the present invention, a liquid crystal dropping method is suitably used, and specifically, for example, a method having the following steps can be mentioned. First, a process is performed in which the sealant for display elements of the present invention is applied by screen printing, dispenser application, or the like to one of two transparent substrates having electrodes such as ITO thin films to form a frame-shaped seal pattern. Next, a process is performed in which minute droplets of liquid crystal are dropwise applied to the entire surface within the frame of the seal pattern, and the other transparent substrate is superimposed under vacuum. After that, a liquid crystal display element can be obtained by a process of irradiating the seal pattern portion with light such as ultraviolet light to provisionally cure the sealant, and a process of heating the provisionally cured sealant to fully cure it. Effect of the Invention

[0072] According to the present invention, it is possible to provide a sealant for a display element, which can provide a display element having excellent reliability even in a high-temperature and high-humidity environment. Also, according to the present invention, it is possible to provide a vertical conductive material and a display element using the sealant for a display element. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0073] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0074] (Examples 1 to 7, Comparative Examples 1 to 5) A sealant for display elements was prepared by mixing each material using a planetary mixer according to the compounding ratios shown in Tables 1 and 2, and then mixing using a three-roll mill. Awatori Rentaro (Thinky Corporation) was used as the planetary mixer. In Tables 1 and 2, "NEM-5000H" is a mixture containing about 50% by weight of a partially methacrylic modified bisphenol A type epoxy compound, about 25% by weight of a bisphenol A type epoxy methacrylate, and about 25% by weight of a bisphenol A type epoxy compound (content of a compound having an epoxy group is about 75% by weight). In Tables 1 and 2, "KRM8287" is a mixture containing about 50% by weight of a partially acrylic modified bisphenol E type epoxy compound, about 25% by weight of a bisphenol E type epoxy acrylate, and about 25% by weight of a bisphenol E type epoxy compound (content of a compound having an epoxy group is about 75% by weight).

[0075] Each of the obtained sealants for display elements was applied to one of two pieces of alkali-free glass, and another piece of alkali-free glass was placed on top of the applied sealant. The sealant was then illuminated with a metal halide lamp at 100 mW / cm 2 After irradiating the glass with ultraviolet light (wavelength 365 nm) for 30 seconds, the other non-alkali glass was peeled off and heated at 120°C for 1 hour to thermally cure the sealant, obtaining a cured product. As the non-alkali glass, OA-10G (manufactured by Nippon Electric Glass Co., Ltd., thickness 0.7 mm, surface roughness 0.2 nmRa) was used. For the obtained cured product, the contact angles with water and methylene iodide (drop amount 3 μL, 30 seconds after dropping) were measured using a contact angle meter at 25°C, and the polar component term was calculated using the above formula. As the contact angle meter, a fully automatic contact angle meter DMo-701 (manufactured by Kyowa Interface Science Co., Ltd.) was used. The results are shown in Tables 1 and 2. Further, each of the obtained sealants for display elements was irradiated with 100 mW / cm using a metal halide lamp. 2 After irradiating with ultraviolet light (wavelength 365 nm) for 30 seconds, the material was heated at 120°C for 1 hour to obtain a cured product. The storage modulus of the obtained cured product was measured at 121°C using a dynamic viscoelasticity measuring device under the conditions of a test piece width of 5 mm, thickness of 0.35 mm, grip width of 25 mm, heating rate of 10°C / min, and frequency of 5 Hz. The temperature at the maximum value of the loss tangent (tan δ) was determined as the glass transition temperature. The dynamic viscoelasticity measuring device used was a DVA-200 (manufactured by IT Keisoku Seigyo Co., Ltd.). The results are shown in Tables 1 and 2. Furthermore, each of the obtained sealants for display elements was irradiated with 100 mW / cm using a metal halide lamp. 2 The cured product was then irradiated with ultraviolet light (wavelength 365 nm) for 30 seconds, and then heated at 120°C for 1 hour to obtain a cured product. The cured product was subjected to a high temperature and high humidity test in which it was exposed to an environment of 121°C, 100% RH, and 2 atm for 24 hours, and the water absorption rate was calculated using the above formula. The results are shown in Tables 1 and 2.

[0076] <Evaluation> The sealants for display elements obtained in the Examples and Comparative Examples were evaluated as follows. The results are shown in Tables 1 and 2.

[0077] (Reliability in high temperature and humidity environments) One part by weight of spacer particles was uniformly dispersed in 100 parts by weight of each sealant for display elements obtained in the examples and comparative examples. Micropearl SI-H050 (manufactured by Sekisui Chemical Co., Ltd.) was used as the spacer particles. The sealant with the spacer particles dispersed therein was filled into a dispenser syringe, degassed, and then applied to a transparent substrate with an alignment film and an ITO thin film using a dispenser so as to draw a rectangular frame. PSY-10E (manufactured by Musashi Engineering Co., Ltd.) was used as the syringe, and SHOTMASTER300 (manufactured by Musashi Engineering Co., Ltd.) was used as the dispenser. Then, minute droplets of liquid crystal were applied dropwise to the entire surface within the frame of the sealant, and immediately another transparent substrate was bonded to it. JC-5004LA (manufactured by Chisso Corporation) was used as the liquid crystal. Immediately after bonding the transparent substrate, a metal halide lamp was used to illuminate the sealant portion at 100 mW / cm. 2 After irradiation with ultraviolet light (wavelength 365 nm) for 30 seconds, the laminate was heated at 120° C. for 1 hour to obtain a liquid crystal display element. For each of the display element sealants obtained in the examples and comparative examples, 20 liquid crystal display elements were produced. The obtained liquid crystal display element was exposed to PCT conditions (121° C., 100% RH, 2 atm) for 24 hours. After exposure to the PCT conditions, the liquid crystal display element was visually observed to confirm the presence or absence of air bubbles. Reliability in a high-temperature, high-humidity environment was evaluated based on the following criteria: if no air bubbles were found in any of the 20 LCD elements, it was marked "◎"; if air bubbles were found in 1 to 3 LCD elements, it was marked "○"; if air bubbles were found in 4 to 8 LCD elements, it was marked "△"; and if air bubbles were found in 9 or more LCD elements, it was marked "X."

[0078] [Table 1]

[0079] [Table 2] [Industrial Applicability]

[0080] According to the present invention, it is possible to provide a sealant for a display element, which can provide a display element having excellent reliability even in a high-temperature and high-humidity environment. Also, according to the present invention, it is possible to provide a vertical conductive material and a display element using the sealant for a display element.

Claims

1. Contains a curable resin and a polymerization initiator and / or a heat curing agent, the curable resin contains a compound having a lactone ring-opening structure, the content of the compound having a ring-opened structure of the lactone is 5 parts by weight or more and 30 parts by weight or less per 100 parts by weight of the curable resin, the polar component term in the surface free energy equation according to the Owens-Wendt method of the cured product is 6.0 or less; The storage modulus of the cured product at 121°C is 50 MPa or more. A sealant for a display element.

2. The curable resin includes a compound having an epoxy group, 2. The sealant for display elements according to claim 1, wherein the content of the compound having an epoxy group is 10 parts by weight or more and 60 parts by weight or less in 100 parts by weight of the curable resin.

3. 3. The sealant for display elements according to claim 1, wherein the cured product has a water absorption rate of 4.0% by weight or less after a high temperature and high humidity test in which the cured product is exposed to an environment of 121° C., 100% RH and 2 atm for 24 hours.

4. A vertical conductive material comprising the sealant for display elements according to claim 1, 2 or 3 and conductive fine particles.

5. A display element comprising a cured product of the sealant for display elements according to claim 1, 2 or 3, or a cured product of the vertical conductive material according to claim 4.

Citation Information

Patent Citations

  • Sealing material for liquid crystal display element and liquid crystal display element using the material

    JP2000066220A

  • Sealing agent for dropping process of LCD panel

    JP2001133794A

  • Sealing agent for liquid crystal display cell, composition for sealing agent for liquid crystal display cell and liquid crystal display element

    JP2002069160A

  • Sealing agent for liquid crystal installation method, vertical conduction material and liquid crystal display element

    JP2009134293A

  • Sealant for liquid crystal dropping method, vertical conduction material, and liquid crystal display element

    JP2015034844A